Urban-touristic Impacts on the Aeolian Sedimentary Systems of the Canary Islands: Conflict Between Development and Conservation - Leví García-Romero; Antonio I. Hernández-Cordero; Elisabeth Fernández-Cabrera; Carolina Peña-Alonso; Luis Hernández-Calvento; Emma Pérez-Chacón (Island Studies Journal, 2016)
Aeolian sedimentary systems in the Canary Islands differ from other European and African systems due to climate, vegetation and isolation. In turn, they experience high human pressure from touristic development. This paper analyzes the impact of urban-touristic development in four aeolian sedimentary systems in the Canaries: Maspalomas, Corralejo, Lambra and Jable Sur. Spatial and surface change variables related to vegetation and geomorphology are obtained by photo-interpretation of historical aerial photography and current orthophotos. Results indicate that systems affected by urban-touristic development have witnessed significant environmental change. In contrast, the systems not impacted by building and construction of infrastructure show minor changes.